THE DETERMINANTS OF STUDENT’S INTENTION TO USE DIGITAL WALLET: Received: 21st December 2022; Revised: 31st December 2023, 12th March 2023; Accepted: 14th March 2023 - Pramusinto, Hengky; Ahmad Nurkhin,; Kardoyo Kardoyo,; Khasan Setiaji,; Dwi Noor Rachmawati Puspadiningrum, (PUPIL: International Journal of Teaching, Education and Learning, 2023)
There are many digital wallets service were used by Indonesian customers during the COVID-19 pandemic. This study aims to analyze the determinants of students' intentions to use digital wallet based on the unified theory of acceptance and use of technology (UTAUT). The research sample is Universitas Negeri Semarang (UNNES) students who have used digital wallet in online purchase transactions. The sampling technique used in this study was incidental sampling. This survey has 135 participants. Data was gathered using questionnaires. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. The study's findings suggest that performance expectations, facilitating conditions, and habits can influence students' intentions to use digital wallet positive and significantly Meanwhile, it was found that effort expectancy, social influence, hedonic motives, and price value were not determinants of students' intention to use digital wallet. The other results show that students' online shopping habits influence their intention and behavior to continue using digital wallet. Students will find it easier to make purchases online. Furthermore, students have high-quality smartphones. The intention and behavior of using digital wallets will significantly increase. The future of research agenda is to explore the theory of online shopping behavior and digital wallet usage.